The role of melatonin in autoimmune and atopic diseases - J.R. Calvo; M.D. Maldonado (AIMS Molecular Science, 2016)
Melatonin is the main secretory product synthesized and secreted by the pineal gland during the night. Melatonin is a pleitropic molecule with a wide distribution within phylogenetically distant organisms and has a great functional versatility, including the regulation of circadian and seasonal rhythms and antioxidant and anti-inflammatory properties. It also possesses the capacity to modulate immune responses by regulation of the TH1/TH2 balance and cytokine production. Immune system eradicates infecting organisms without serious injury to host tissues, but sometimes these responses are inadequately controlled, giving rise to called hypersensitivity diseases, or inappropriately targeted to host tissues, causing the autoimmune diseases. In clinical medicine, the hypersensitivity diseases include the allergic or atopic diseases and the hallmarks of these diseases are the activation of TH2 cells and the production of IgE antibody. Regarding autoimmunity, at the present time we know that the key events in the development of autoimmunity are a failure or breakdown of the mechanisms normally responsible for maintaining self-tolerance in B lymphocytes, T lymphocytes, or both, the recognition of self-antigens by autoreactive lymphocytes, the activation of these cells to proliferate and differentiate into effector cells, and the tissue injury caused by the effector cells and their products. Melatonin treatment has been investigated in atopic diseases, in several animal models of autoimmune diseases, and has been also evaluated in clinical autoimmune diseases. This review summarizes the role of melatonin in atopic diseases (atopic dermatitis and asthma) and in several autoimmune diseases, such as arthritis rheumatoid, multiple sclerosis, systemic lupus erythematosus, type 1 diabetes mellitus, and inflammatory bowel diseases.